Rethinking Public Procurement in the context of Socio-technical Transitions - Trindade, Paula Cristina Cayolla Morais (2018)
Addressing sustainable development requires a “transition” or “system innovation” away from the current socio-technical system. In Europe, the focus of sustainability policies moved from the supply to the demand side, in which public procurement plays a prominent role. This interest is spreading through authorities at different government levels, resulting in a market factor with enormous potential to shape production and consumption trends. This thesis explores how public organizations can re-think the procurement process, raising their ambitions and broadening their vision, changing their organizational approach towards culture, strategies, structures, and practices, contributing to the emergence of socio-technical transitions or sustainability transitions. The research contributed to the literature by developing an analytical framework linking the fields of public procurement and transitions, constituted by two complementary instruments: the STP Model, which prescribes practices that influence the transformation of socio-technical systems, integrating different approaches to public procurement, (green, sustainable and innovation procurement), in a three-level structure (niche, regime, and landscape); and, the STP Process, which introduces a dynamic perspective of the process of using public procurement as a governance mechanism in the context of socio-technical transitions. The STP Model was further operationalized into a practical tool - the SPP toolbox-- to support public organizations in the process of re-thinking the procurement process. The SPP Toolbox incorporates different approaches at different levels, including procurement practices (GPP, SPP, PPI), as well as the organizational and inter-organizational dimensions, into one tool. This allows for flexibility in the objectives to be achieved, which can be developed in increasing degrees of complexity, according to the characteristics, experience, and knowledge of the organization. Finally, the SPP Toolbox was tested in case studies and in different contexts, showing that public organizations of different types – regarding dimension, organizational structure, purchasing power and level of experience – were able to improve the performance, ambition, and vision of their procurement practices by implementing the tool, providing evidence for part of the STP Model and the STP Process.